Implementation of Stad-cooperative Learning in Improving Social Skills of College Student - Rizkan Syahbuddin; Erik Perdana Putra; Haryono Haryono (Universitas Pakuan, 2022)
This study aims to determine the difference in the average social skills of students with the STAD type cooperative learning model and the conventional learning model in the form of direct learning in social studies education courses. The research method used is descriptive and quantitative with a quasi-experimental research design with a post-test only non-equivalent control group design. This study begins with a normality test and a homogeneity test of variance. The results of the study show that in hypothesis testing with t-test obtained p-value (sig) of 0.000 with a significant level of 0.05, because 0.000 0.05 then H0 is rejected. And the results of the calculation of social skills analysis, the average value of social skills in the experimental group is 0.597812 and the control group is 0.208414. From these results it can be concluded that the average social skills in the experimental group is better than the average in the control group. So it is known that there is a significant difference in average social skills between students who are treated with the STAD type cooperative learning model with conventional learning in social studies education courses at Tadris IPS UIN Fatmawati Sukarno Bengkulu.